Pro Microsoft Hyper-V 2019 Practical Guidance and Hands-On Labs - Syrewicze, Andy (Apress, 2018)
Successfully create and manage your Hyper-V environment without any of the marketing fluff. This book's lab-driven, hands-on approach will get you up and running as quickly and efficiently as possible. Virtualization is the cornerstone of today's data center. As a modern-day IT pro, you are required to manage environments that are in a regular state of flux and increasing in both size and complexity. To keep up, you need practical information in a format that is succinct, yet comprehensive and highly applicable. Pro Hyper-V 2019 breaks down critical and time-saving topics into a series of easy-to-digest chapters, showing you how to perform Hyper-V management tasks using both GUI and PowerShell-based tools. Building on your existing knowledge of Windows Server management, Active Directory, networking, and storage, experts and Microsoft MVPs Syrewicze and Siddaway begin with a foundation of why computing workloads are virtualized. This is followed by chapters covering the range of management tasks associated with virtualized environments, including: managing hosts and guest machines; networking, storage, and high availability (host and guest); disaster recovery and virtual machine migration; and monitoring. What You'll Learn: Apply practical information to administer your Hyper-V environments Understand multiple administration styles (GUI, command line, and automation) Written by IT pros for IT pros - just the information you really need without the padding Administer and use containers Utilize hands-on labs to learn about storage, networking, and high availability This book is for IT administrators tasked with implementing Hyper-V environments or migrating from VMware. IT pros joining a team that is responsible for managing Hyper-V and "lone administrators" covering the gamut in smaller organizations will also find this book indispensable. Andy Syrewicze is Technical Evangelist for Altaro Software, makers of Altaro VM Backup. In that role he does podcasts, webinars, blogging, public speaking, and serves as chief editor for all Altaro blog platforms. Prior to that, Andy spent 15 years providing technology solutions across several industry verticals. Andy is a 4-time Microsoft MVP focused on virtualization, cloud services, and the Microsoft Server Stack. Richard Siddaway has worked with Microsoft technologies for more than 25 years, predominantly in the IT sector. He has designed, built, and managed numerous enterprise-level systems, including implementation of virtualized environments for organizations. Richard is a Microsoft MVP (11 years and counting), an author, and a regular speaker on the North America and Europe speaker circuit.